Potential of multivariate analysis in substance abuse research - Hafizan, Juahir; Mohd Khairul Amri, Kamarudin; Mohd Ekhwan, Toriman; Siti Nor Fazillah, Abdullah (2017)
Substance abuse has a close association with health and social problems. This study demonstrates the usefulness of multivariate statistical analysis in substance abuse studies. Applying multivariate analyses such as the factor analysis, principal component analysis cluster analysis and discriminant analysis in other studies gives a view on how this method can be applied in the substance abuse field. To date, there are limited studies on applying this powerful method in this study. However, looking forward on the capability of the multivariate analysis on handling and interpreting the complexity of the data, some potential goals that can be achieved in substance abuse study can be highlighted.